2018
DOI: 10.1016/j.scitotenv.2018.05.348
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of temperature and salinity oscillations on a key mesopredator fish from European coastal systems

Abstract: A population dynamics model was developed to assess the short and long-term effects of temperature and salinity variations in the common goby Pomatoschistus microps in a Portuguese estuary (Minho estuary, NW Portugal). The population was divided into juveniles, females and males, which constituted the model's state variables. Linear regressions between the observed and the predicted density of juveniles, females and the total population were significant. Parameter's sensitivity and uncertainty analysis were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Several studies reported the influences of water salinity and temperature on fish larval development and growth. Simulations through the model to assess the effects of climatic changes in the fish population by Souza et al (2018) indicated that the common goby population is sensitive to both temperature and salinity changes. Overall, scenarios of more than 3 °C increase caused significant population decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the influences of water salinity and temperature on fish larval development and growth. Simulations through the model to assess the effects of climatic changes in the fish population by Souza et al (2018) indicated that the common goby population is sensitive to both temperature and salinity changes. Overall, scenarios of more than 3 °C increase caused significant population decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Abundance of fish in Greenland waters can be influenced by local and external physical and biological processes. Local processes may consist of changes affecting fish growth, reproduction and survival, while changes in conditions in adjacent areas could as well affect migration or drift patterns of early life stages and thereby affect local abundance (Biro et al, 2010; Dahlke et al., 2018; Kuczynski et al, 2017; Souza et al, 2018). As local temperature is not the only mechanistic driver of these processes, we discuss the role of temperature and other pathways linked to the distribution of mode waters in the North Atlantic as guidance for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Increased temperature and salinity may alter fish assemblage structure; this may lead to an impact on all feeding levels of fish that feeding on phytoplankton and small fishes (Beaugrand, 2009). The variations in these parameters (temperature and salinity) will have strongly impact on small-sized fish communities which reinforce connective position in food webs (Souza et al, 2018). The results revealed a noticeable rise in the concentrations of salinity from May to October due to low water levels, as well as higher temperatures which lead to increase evaporation rates (Abdullah et al, 2017).…”
Section: Discussionmentioning
confidence: 99%